Formality in Academic Writing: Investigating Stylistic Competence of Undergraduate EFL Learners - Akhtar, Raheela; Riaz, Mehvish (University of Wah Journal of Social Sciences, 2019)
Academic writing is expected to be formal. The study, therefore, investigates the extent to which written text created by undergraduate learners of English as a foreign language is formal or informal. For this purpose, essay writing projects given to a class of 30 students of BS in Arts at Government Postgraduate Islamia College for Women, Faisalabad have been selected. The framework for analysis has been adopted from the frameworks of formality and informality suggested by Heylighen and Dewaele (1999) and Chang and Swales (1999), respectively. The analysis has been made by checking the frequencies of first-person pronouns, unattended anaphoric pronouns, conjunctive adverbs, sentence final preposition, listing expressions, second person pronouns, contractions, direct questions, exclamations to examine informality; while, prepositional phrases, larger and different words in the form of adjectives, verbs, adverbs and nouns, longer sentences and coherence markers to examine formality. Results of the study have implications for language testing, curriculum design, genre analysis and methods for teaching academic writing. There is paucity of research in this area in Pakistani context; therefore, the study not only contributes to the existing literature, but it can also help improve teaching and assessment methods for teaching essay writing to undergraduate students in Pakistani colleges.